The Dual Role of Saddu Al-Dzari’ah: An Ijtihad Method in Islamic Law Sources and a Case Analysis Approach - Manggala, Kayan; Hamidah, Tutik (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 4 (2024): The 7th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2024)
Saddu Al-Dzari'ah as a Method of Ijtihad in Islamic Legal Sources has been widely discussed in scholarly discourse. It is frequently employed as an analytical approach to address contemporary issues not explicitly mentioned in primary sources, such as Bitcoin, COVID-19, early marriage, and other novel phenomena. However, existing research has yet to comprehensively examine its dual role as a method of ijtihad in Islamic legal sources and as a case analysis approach, simultaneously. The objectives of this study are: (1) to understand the meaning of Saddu Al-Dzari'ah, (2) to explore its role as a method of ijtihad and source of Islamic law, and (3) to investigate its function as a case analysis approach. This study employs a literature review with a descriptive-analytical approach, utilizing both primary and secondary sources. The findings of this research are as follows: (1) Etymologically, Saddu means barrier, obstacle, or blockage, while Dzari'ah refers to a means or intermediary. Terminologically, it refers to the act of closing or blocking all pathways that lead to disobedience or harm; (2) Saddu Al-Dzari'ah’s role as a method of ijtihad is supported by its integration with the Qur'an and Hadith; and (3) the concepts of Dzari'ah proposed by scholars such as Ibn Qayyim and Abu Ishaq al-Shatibi are categorized into four types and have been applied in various published articles